2004
DOI: 10.1002/hbm.20021
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of syntactic transformations

Abstract: Many agrammatic aphasics have a specific syntactic comprehension deficit involving processing syntactic transformations. It has been proposed that this deficit is due to a dysfunction of Broca's area, an area that is thought to be critical for comprehension of complex transformed sentences. The goal of this study was to investigate the role of Broca's area in processing canonical and non-canonical sentences in healthy subjects. The sentences were presented auditorily and were controlled for task difficulty. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 53 publications
4
12
0
Order By: Relevance
“…Interestingly, the sentence complexity and taskdemand conditions did not interact (i.e., the task effect was equally robust for SR and OR sentences). We note that this finding of no different localization of subject and object relative constructions in terms of L-IFC activation is in line with the current work of Fiebach et al (2004) and Wartenburger et al (2004) who investigated canonical and non canonical forms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the sentence complexity and taskdemand conditions did not interact (i.e., the task effect was equally robust for SR and OR sentences). We note that this finding of no different localization of subject and object relative constructions in terms of L-IFC activation is in line with the current work of Fiebach et al (2004) and Wartenburger et al (2004) who investigated canonical and non canonical forms.…”
Section: Discussionsupporting
confidence: 92%
“…Most of this work has implicated left anterior frontal brain regions, specifically including Broca's area, in the processing of sentences with complex structure (Ben-Shachar et al, 2003;Caplan et al, 1998Caplan et al, , 1999Caplan et al, , 2001Cooke et al, 2001;Dapretto and Bookheimer, 1999;Friederici et al, 2000;Grossman et al, 2002;Heim et al, 2003;Inui et al, 1998;Just et al, 1996;Musso et al, 2003;Newman et al, 2001;Ni et al, 2000;Sakai et al, 2001;Stromswold et al, 1996;Waters et al, 2003;Wartenburger et al, 2004). In general, conclusions drawn from this research fit well with behavioral and lesion evidence gleaned over decades about the role of left inferior frontal cortex (L-IFC) including Broca's area.…”
Section: Introductionsupporting
confidence: 73%
“…Overall accuracy in sentence comprehension, regardless of morphosyntactic structure, was associated with the left middle posterior superior temporal gyrus and inferior parietal lobule, a finding that is consistent with previous studies of sentence com- prehension (Just et al, 1996;Stromswold et al, 1996;Carpenter et al, 1999;Dapretto and Bookheimer, 1999;Ni et al, 2000;Friederici et al, 2003;Ben-Shachar et al, 2004;Wartenburger et al, 2004). In the present study, the left temporal area showed a correlation with overall sentence comprehension abilities, but not with nonsyntactic vWM abilities, supporting its specificity for sentence processing.…”
Section: Discussionsupporting
confidence: 92%
“…These sentences are "noncanonical" because of their atypical word order and can be difficult to understand for patients with Broca's aphasia. However, they do not consistently elicit left frontal activations in functional neuroimaging experiments when compared with active structures (Caplan, 2000;Ni et al, 2000;Wartenburger et al, 2004). Consistently, type 2 word order sentences (which included passives) only showed a trend for correlation with the same left frontal region that correlated significantly with type 3 multiclausal relatives.…”
Section: Discussionmentioning
confidence: 98%
“…For example, experimenters have manipulated the relative syntactic complexity of sentences. Compared to simple sentences, syntactically complex sentences are thought to make greater demands on resources such as working memory and transformational analysis of misplaced syntactic fragments (Wartenburger et al, 2004). Given that the number of words was controlled in these studies, however, the relative amount of low-level constituent parsing should be fairly equivalent across conditions.…”
Section: Introductionmentioning
confidence: 99%